2015
DOI: 10.1177/1941738115579030
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Failed Anterior Cruciate Ligament Reconstruction With Autograft Compared With Allograft in Young Patients

Abstract: Context:The advantages of allograft anterior cruciate ligament reconstruction (ACLR), which include shorter surgical time, less postoperative pain, and no donor site morbidity, may be offset by a higher risk of failure. Previous systematic reviews have inconsistently shown a difference in failure prevalence by graft type; however, such reviews have never been stratified for younger or more active patients.Objective:To determine whether there is a different ACLR failure prevalence of autograft compared with all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 79 publications
2
60
0
2
Order By: Relevance
“…It has been reported by us, others, and confirmed by a meta-analysis that allograft ACLRs have a high retear risk compared to autografts in younger and/or highly active athletes 11, 3238 . In this group, the use of allograft tissue (as well as youth and high activity) was a predictor of graft retear in the early time frame.…”
Section: Discussionsupporting
confidence: 62%
“…It has been reported by us, others, and confirmed by a meta-analysis that allograft ACLRs have a high retear risk compared to autografts in younger and/or highly active athletes 11, 3238 . In this group, the use of allograft tissue (as well as youth and high activity) was a predictor of graft retear in the early time frame.…”
Section: Discussionsupporting
confidence: 62%
“…[41][42][43] In a systematic review and meta-analysis, 41 Yao et al found a significant difference in clinical failure in favor of autograft. However, the grafts they evaluated were patellar tendon.…”
Section: Discussionmentioning
confidence: 99%
“…These secondary outcome measures were evaluated through patient completion of validated knee surveys for evaluation of functional status: IKDC subjective knee evaluation form and the University of California at Los Angeles (UCLA) ACL-QL questionnaire. 7,14,20 Rehabilitation…”
Section: Methodsmentioning
confidence: 99%
“…1 The optimal graft for ACL reconstruction is a heavily debated topic and numerous studies have been conducted to determine the optimal graft for the patient. [1][2][3][4][5][6][7] Recently, autograft ACL reconstruction has been shown to have a lower rerupture rate, predominantly in younger, physically active subjects when compared with allograft tissue. 1,8,9 In addition, the use of allograft tissue in young athletic patients, especially in those less than 25 years of age, has recently been questioned because of documented failures rates as high as 23% with allograft compared with 6% with autograft.…”
mentioning
confidence: 99%